Implementasi Pendidikan Karakter Dalam Pembelajaran IPS Melalui Media Pop Up Book - Ma'ruf Mustofa; Hawwin Fitra Raharja (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
Nowadays, there are many phenomena that show that the Indonesian nation is experiencing a moral decline, where politeness to parents is expensive and covered by a sense of mutual indifference. This is caused by several factors, one of which is the entry of foreign cultures into the Indonesian nation. The use of media is also very influential on the enthusiasm of students in participating in learning. It is hoped that the selection of media can encourage students and can cultivate good characters for the students of SDIT Darul Falah Cukir Jombang..This type of research is a mixed method research. This study uses one class. The subjects were fourth grade teachers and fourth grade students at SDIT Darul Falah Cukir. And the object is character education. Data collection techniques in this study are observation, interviews, questionnaires, and documentation. Data analysis in this study was carried out by collecting data, reducing data, presenting data and drawing conclusions. While the validity of the data using triangulation, namely sources, techniques and time, and peer discussion. The results showed: Planning to make lesson plans and prepare learning media, The implementation is carried out in two stages, These results can be seen from the Pop Up Book media trial through student response questionnaires, showing that an average of 37.5 proves that the character of students has increased, The inhibiting factors for the Pop Up Book media include the program, infrastructure, character building, and time for making media, Supporting factors for Pop Up Book media include the existence of discipline, good cooperation and interaction between school residents and students, and support from parents.